The Effect of Participatory Rural Appraisal (Pra) in Bccpgle Activities on the Community Welfare in Batu Itam Village, Aceh Selatan Regency, Nanggroe Aceh Darussalam Province - Pratama, Rio; Purwoko, Agus; Rujiman (Journal of Environmental and Development Studies, 2021)
The participatory rural appraisal method is carried out as an effort to develop areas and improve human resources and community welfare. The purpose of this study was to determine the effect of village transect, seasonal calendar, division of labour between men and women, livelihood, and institutional relation partially and simultaneously on the community welfare. The study was conducted in Batu Itam Village on the effect of participatory rural appraisal on the community welfare. The analytical methods employed descriptive analysis and multiple regression analysis. The results showed that the village transect, seasonal calendar, labor division between men and women, and livelihood had a positive and significant effect on the community welfare. Institutional relation had no significant effect on the community welfare. Village transect, seasonal calendar, labor division between men and women, livelihood, and institutional relation simultaneously had a significant effect on the community welfare in Batu Itam Village, South Aceh Regency